An Assessment of Secondary School Learners’ Performance in Economics in the OR Tambo Inland District, Eastern Cape Province South Africa - Comfort Wendane; Zikhona Seleke (Journal of Education and Learning Technology)
The aim of this study is to examine the factors that influence learners’ performance in economics as a subject. This study used a mixed methodology which combined qualitative and quantitative methods, providing a more thorough comprehension of the study problem. The qualitative method was employed to collect data through interviews with teachers. The quantitative method was also used to collect data through questionnaires from learners and teachers. The study targeted four economics teachers within the school and 15 learners in the Further Education and Training (FET) phase with different socioeconomic backgrounds and academic abilities. The results of this study revealed that the lack of motivation, and time allocated for studying economics is very limited to cover the workload and the lack of teachers who are experienced in teaching economics. Results focused on student interest in the subject, teacher skills and specialization, and degrees of knowledge regarding the benefits of studying economics as factors that influence their performance. The study recommends that teachers should motivate and enlighten learners about the benefits of Economics and school authorities should appoint only qualified and competent teachers to teach Economics and there should be language policies to deal with language proficiency. This study adds to existing literature on students’ performance in Economics in South African secondary schools.